Evaluation of Halitosis and Sialometry in Emirati Diabetic Patients before and after Periodontal Treatment - Hossam Abdelatty Eid Abdelmagyd; Prabhu Manickam Natarajan; Walid Shaaban Moustafa Elsayed (Institute of Medico-legal Publications Pvt Ltd, 2021)
Halitosis is an important social complaint which affects both healthy and periodontally diseased individuals.Oral malodor is mainly caused by a microbial degradation of both sulfur-containing and nonsulfur-containingamino acids into volatile, bad-smelling gases. Anaerobic gram-negative bacteria, the same species that havebeen linked to periodontal diseases, are especially involved in this process, explaining the link between oralmalodor with periodontitis. The following study was done to investigate the parameters of halitosis andsialometry of Emirati diabetic patients in correlation with oral concentration of volatile sulfur compounds(VSC), salivary flow rate before and after non-surgical periodontal treatment (scaling & root planning) forpatients having moderate Generalized and/localized chronic periodontitis.Subjects and Methods: Eighty-one (81) Emirati subjects volunteers were recruited from the dental hospital,with average age 38-49 years. They have been divided into in three groups: Group I (negative control),Group II, and Group III and Group IIIa. Halitosis measurements for all volunteers had been recorded usingGas Chromatography. For group III samples were collected before periodontal treatment, and subsequentlyat two- & four-weeks following start of non-surgical periodontal treatment (Scaling & root planning).Results: There were 54 patients participated in this study. Of the 54, 27 were control and the remainingwere controlled DM. The mean and SD of all variables before and after the intervention showed that thevalues of all variables reducing after the intervention. All the difference observed was statistically significant(P<0.001). This study observed that the mean value of unstimulated salivary flow rate and stimulated salivaryflow rate was less in the controlled DM group compared to control group, but for probing picker depth, CALand average bone loss was more in controlled DM group compared to control group.Conclusion: Based on the findings, it can be stated that diabetes is a major risk factor for periodontitis, andthe risk of periodontal disease increases if glycemic control is poor; it was also proved beyond doubt thatpeople with poorly controlled diabetes are at an increased risk of periodontal disease and loss of alveolarbone. Controlling diabetes by successfully improving glycemic control will reduce the risk and severity ofperiodontal diseases.